(untitled) (ETIMA, 2024)
Heating power plants are the major source of hot water intended for heating of communal areas or districts, or even whole cities for any developed country on a large scale. The usual concept for conventional heating power plants is burning fuel into combustible chambers called boilers and production of heat in the form of hot water. Then, using already developed heat network consisted of pipes and pumps, the hot water is distributed to final customers. At the cogeneration power plants, the process is almost similar, with the major difference that in the boilers instead of hot water, the so-called superheated water vapor is generated which initially is used in the steam turbinesfor electricity generation, and later the exhausted steam is re-used using condensers for production of heat in the form of hot water for central heating purposes. In this paper, the authors present comparative environmental analysis between two gas-fired plants used for central heating of the city of Skopje. The first one is the conventional gas-fired heating plant which has only one product, hot water for central heating purposes. The second power plant is cogeneration gas-fired power plant; thus, it simultaneously generates electricity and heat used for central heating. Since 2013, both plants use natural gas as primary fuel, which although still a fossil fuel, is less polluting and environmentally more acceptable. The obtained results of the analysis and comparison between both power plants are given in details showing that both plants are within the prescribed environmental regulations.